Semi-direct composite overlay restoration as an alternative restoration for endodontically treated tooth: a case report - Brians, N.; Gunawan, J. A.; Prahasti, A. E.; Istanto, E.; Mohamed Khazin, Sobrina (CRC Press, Taylor & Francis Group, 2024)
Background(s): Endodontically treated teeth are structurally different from vital teeth. There are significant changes including loss of tooth structure and physical characteristics. The loss of hard tissue due to decay, crack, or cavity preparation increases the risk of crown and root fracture over time. The aim of restoration is to protect the remaining tooth and replace the missing tooth structure. Semi-direct technique restoration using resin composite material can be an alternative to restoring endodontically treated teeth by covering the missing tissue. Various combinations of light polymerization and heat treatment are claimed to increase the mechanical properties restoration. Case report(s): A 52-year-old female requested for restoration on her endodontically treated tooth 47. The tooth presented with a provisional restoration large defect on the occlusal-lingual surface. The patient has financial limitations, and requested for an alternative restoration besides indirect restoration. The patient also has limited mouth opening. Case Management(s): After examination, semi-direct overlay restoration was opted for the patient. An overlay cavity was prepared and an impression was taken. A working die model was fabricated using silicone. The composite overlay was fabricated chairside extra-orally with several lab treat-ments to increase its mechanical properties. The overlay was cemented and polished in a single visit. Conclusion(s): Clinicians can restore endodontically treated teeth successfully using the semi-direct technique that counters the disadvantages of the indirect technique, such as saving appointment time, cost, and an increase in mechanical properties compared to the direct technique. It is an alternative restoration that combines the advantages of the direct and indirect techniques resulting in satisfactory function and esthetic outcome.